(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article substantiates the relevance of the study of historical time in the context of a polysyllabic system of unity of concepts past – present – future. At the same time, these concepts are considered taking into account the unity of the moments of stability and variability of the development process. It is thanks to the unity of these two components of development that it is possible to most fully analyze the relationship of the three dimensions of time both in the structural-functional and in the historical-cognitive aspects. The study of the time paradigm in this regard allows us to most clearly identify the features of changes in human existence in a particular period of time. In this sense, time is an important part of the worldview coordinate system.